2016
DOI: 10.1136/bcr-2016-216991
|View full text |Cite
|
Sign up to set email alerts
|

PathogenicSarcinain urine

Abstract: Sarcina is a Gram-positive anaerobic coccus that has been consistently reported in the upper gastrointestinal tract biopsies of patients with evidence of gastric stasis. The pathogenic role of Sarcina in humans is not entirely known. We describe an infant who was surgically treated for posterior urethral valve and the urine showed pathogenic Sarcina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The stomach is the most frequent site of bacterial identification (36 cases, 77%), followed by esophagus (7 cases, 15%) and duodenum (6 cases, 13%). The bacteria were also identified in the blood (two reports) 12,37 and urine (one report) 25 cultures. There is a report of the bacterium found in a pneumonectomy specimen.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The stomach is the most frequent site of bacterial identification (36 cases, 77%), followed by esophagus (7 cases, 15%) and duodenum (6 cases, 13%). The bacteria were also identified in the blood (two reports) 12,37 and urine (one report) 25 cultures. There is a report of the bacterium found in a pneumonectomy specimen.…”
Section: Discussionmentioning
confidence: 98%
“…48 The pathogenicity of Sarcina ventriculi in humans is not fully understood, and it has been isolated from different sites of the gastrointestinal, urinary and respiratory tracts, as wells as in blood, in different clinical settings. 12,21,25 There is a hypothesis that the bacteria could damage the gastrointestinal mucosa through the accumulation of acetaldehyde. 46 In our literature review, we identified forty-five cases reports, and here we described two more cases of the bacterial diagnosis, identified by microscopic morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcina is an anaerobic gram-positive coccus that grows in low-PH environments, commonly found in the upper gastrointestinal tract. However, some extra-intestinal localizations are also reported (Bommannan et al, 2016). Sarcina has been described in both pediatric and adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…After a full-text review, all the remaining articles were considered eligible and were included in the systematic review. Thus, a total of 55 articles reporting 65 cases of SV were found (Aggarwal et al, 2018;Alvin et al, 2018;Behzadi et al, 2017;Berry et al, 2015;Bhagat et al, 2015;Bommannan et al, 2016;Bortolotti et al 2019;Canan et al, 2017;Carrigan et al, 2015;Chan et al, 2020;Chougule et al, 2015;Cox II et al, 2020;Darch et al, 2016;De Meij et al, 2017;Dey et al, 2019;DiMaio et al, 2014;Dolganiuc et al, 2017;Dumitru et al, 2020;Elvert et al, 2018;Fanaroff et al, 2020;Gulati et al, 2019;Haroon Al Rasheed et al,2016;Heidinger et al, 2020;Hillman et al, 2020;Karakus et al, 2014;Khan et al, 2016;Kulkarni et al, 2013;Kumar et al, 2014;Laass et al, 2010;Lam-Himlin et al, 2011;Liu et al, 2018;Lopez et al, 2020;Louis et al, 2014;Medlicott et al, 2015;Mironova et al, 2017;Nepplet et al, 2018;Perrault et al, 2021;Perrault et al, 2021;Propst et al, 2020;Rajasekar et al, 2016;Ratuapli et al, 2013;…”
Section: Study Selectionmentioning
confidence: 99%
“…None of these reports of esophageal disease are based upon brushing cytology diagnoses and rather emphasize surgical pathologic techniques and confirmatory molecular microbiology studies. Cytologic identification of Sarcina bacteria has been previously reported in urine and as a secondary diagnosis in a fine‐needle aspiration biopsy of a gastric adenocarcinoma . No prior reports of Sarcina diagnosed by esophageal brushing cytology exist.…”
mentioning
confidence: 99%